Correlation Between Pyridoxal 5’-Phospate Level And Valproic Acid In Epilepsy Children - I Gusti Ngurah Made Suwarba; Ni Putu Yunik Novayanti; I Gusti Lanang Sidiartha; Dewi Sutriani Mahalini (Molecular and Cellular Biomedical Sciences, 2019)
Background: It is important to maintain the adequate level of vitamin B6 to ensure stable metabolism. Vitamin B6 serum level might decreased by absorption disturbance or increasing demand. Valproic acid increase the synthesis of serum GABAergic in the other hand vitamin B6 is required as cofactor for gamma-amino butyric acid (GABA) formation. The dosage and duration of valproic acid therapy might be correlated with vitamin B6 serum level. The aim of this study is to know the correlation between vitamin B6 serum level against dosage and duration of valproic acid therapy in children with epilepsy.Materials and Methods: This is a cross sectional study to investigate the correlation between vitamin B6 serum level against dosage and duration of valproic acid therapy. The level of vitamin B6 serum was determined by checking vitamin B6 active form in serum, pyridoxal 5’-phospate (PLP).Results: In this study, 37 epilepsy children with valproic acid duration therapy more than 3 months was enrolled. Fifty six percent epilepsy children were male, commonly on children age 1-5 years old. Spearman correlation coefficient test showed a significant weak negative correlation between vitamin B6 serum level and dosage of valproic acid (r=–0.35; p=0.03), and very weak negative correlation with valproic acid duration therapy (r=-0.08; p=0.59), however it was not significant. Conclusion: There was a significant weak negative correlation between vitamin B6 serum level and very weak negative correlation with valproic acid duration therapy, but not significant in children with epilepsy.Keywords: correlation, valproic acid, vitamin B6